We will learn how to find the equation of a line parallel to a line.
Prove that the equation of a line parallel to a given line ax + by + λ = 0, where λ is a constant.
Let, ax + by + c = 0 (b ≠ 0) be the equation of the given straight line.
Now, convert the equation ax + by + c = 0 to its slope-intercept form.
ax + by+ c = 0
⇒ by = - ax - c
Dividing both sides by b, [b ≠ 0] we get,
y = -\(\frac{a}{b}\) x - \(\frac{c}{b}\), which is the slope-intercept form.
Now comparing the above equation to slope-intercept form (y
= mx + b) we get,
The slope of the line ax + by + c = 0 is (- \(\frac{a}{b}\)).
Since the required line is parallel to the given line, the slope of the required line is also (- \(\frac{a}{b}\)).
Let k (an arbitrary constant) be the intercept of the required straight line. Then the equation of the straight line is
y = - \(\frac{a}{b}\) x + k
⇒ by = - ax + bk
⇒ ax + by = λ, Where λ = bk = another arbitrary constant.
Note: (i) Assigning different values to λ in ax + by = λ we shall get different straight lines each of which is parallel to the line ax + by + c = 0. Thus, we can have a family of straight lines parallel to a given line.
(ii) To write a line parallel to a given line we keep the expression containing x and y same and simply replace the given constant by a new constant λ. The value of λ can be determined by some given condition.
To get it more clear let us compare the equation ax + by = λ with equation ax + by + c = 0. It follows that to write the equation of a line parallel to a given straight line we simply need to replace the given constant by an arbitrary constant, the terms with x and y remain unaltered. For example, the equation of a straight line parallel to the straight line 7x - 5y + 9 = 0 is 7x - 5y + λ = 0 where λ is an arbitrary constant.
1. Find the equation of the straight line which is parallel to 5x - 7y = 0 and passing through the point (2, - 3).
Solution:
The equation of any straight line parallel to the line 5x - 7y = 0 is 5x - 7y + λ = 0 …………… (i) [Where λ is an arbitrary constant].
If the line (i) passes through the point (2, - 3) then we shall have,
5 ∙ 2 - 7 ∙ (-3) + λ = 0
⇒ 10 + 21 + λ = 0
⇒ 31 + λ = 0
⇒ λ = -31
Therefore, the equation of the required straight line is 5x - 7y - 31 = 0.
2. Find the equation of the straight line passing through the point (5, - 6) and parallel to the straight line 3x - 2y + 10 = 0.
Solution:
The equation of any straight line parallel to the line 3x - 2y + 10 = 0 is 3x - 2y + k = 0 …………… (i) [Where k is an arbitrary constant].
According to the problem, the line (i) passes through the point (5, - 6) then we shall have,
3 ∙ 5 - 2 ∙ (-6) + k = 0
⇒ 15 + 21 + k = 0
⇒ 36 + k = 0
⇒ k = -36
Therefore, the equation of the required straight line is 3x - 2y - 36 = 0.
● The Straight Line
11 and 12 Grade Math
From Equation of a Line Parallel to a Line to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Jun 21, 24 02:19 AM
Jun 21, 24 01:59 AM
Jun 21, 24 01:30 AM
Jun 21, 24 01:00 AM
Jun 19, 24 09:49 AM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.